Comparison of autophotomontage software programs in eyes with CMV retinitis - Chen,J. (Association for Research in Vision and Ophthalmology Inc., 2015)
Purpose. Automated mosaic software programs are used to stitch together overlapping retinal fundus photographs. The performance of these programs in eyes with retinal diseases has not been independently evaluated. This study compares the quality of the mosaic products of three autophotomontage software programs, using digital fundus photographs of eyes with cytomegalovirus (CMV) retinitis. Methods. Photographs of 99 eyes with CMV retinitis of 94 patients with HIV were taken at Maharaj Nakorn Chiang Mai Hospital in Chiang Mai, Thailand. Automated mosaic images were created for each of the 99 eyes by three different commercially available programs: IMAGEnet (Topcon, Oakland, NJ), i2k Retina (DualAlign LLC, Clifton Park, NY), and AutoMontage (OIS, Sacramento, CA). Three masked graders ranked each set of mosaics for each eye. The graders also assessed the overall image quality and documented mosaic artifacts in each image. Results. i2k Retina was ranked as the best program (70%-88%) more often than AutoMontage (10%-33%, P < 0.001) or IMAGEnet (0%-4%, P < 0.001) for creating automontages from digital fundus photographs of eyes with CMV retinitis. Acceptable quality mosaic images were reported most commonly for i2k Retina (93%-94%) and AutoMontage (91%-95%), followed by IMAGEnet (27%-56%, P < 0.001). IMAGEnet had a significantly higher percentage of mosaic errors than did either i2k Retina or AutoMontage (P < 0.001). Conclusions. In eyes with CMV retinitis, both the i2k Retina and AutoMontage software packages appear to create higher quality mosaics than does IMAGEnet. Automated retinal mosaic imaging may be valuable in diagnosing CMV retinitis and observing disease progression. © 2011 The Association for Research in Vision and Ophthalmology, Inc.